Self-reported risky sexual practices among adolescents and young adults in Botswana - Unoda Chakalisa; Kathleen Wirth; Kara Bennett; Etienne Kadima; Kutlo Manyake; Tendani Gaolathe; Pam Bachanas; Tafireyi Marukutira; Refeletswe Lebelonyane; Scott Dryden-Peterson; Lisa Butler; Mompati Mmalane; et al. (Southern African Journal of HIV Medicine, 2019)
Background: Adolescents and young adults account for more than one-third of incident Human Immunodeficiency Virus (HIV) infections globally. Understanding sexual practices of this high-risk group is critical in designing HIV targeted prevention programming.